Trinuclear magnesium complexes stabilized by aminoalkoxide ligands. Issue 17 (1st September 2016) - Kim, Hyo-Suk; George, Sheby Mary; Jung, Eun Ae; Han, Jeong Hwan; Park, Bo Keun; Son, Seung Uk; Kim, Chang Gyoun; Chung, Taek-Mo
Abstract: New magnesium complexes, [Et2 Mg3 (dmamp)4 ] (1 ) and [(CH2 =CH)2 Mg3 (dmamp)4 ] (2 ), were prepared by the reaction of alkylmagnesium bromide with sodium 1-dimethylamino-2-methyl-2-propoxide [Na(dmamp)] in THF. Complexes1 and2 were characterized by 1 H and 13 C NMR spectroscopies, FTIR spectroscopy, elemental analysis, and single-crystal X-ray diffraction (XRD) analysis. The XRD analysis showed that these complexes are trinuclear where the alkoxy O is the μ2 -O bridge between the Mg ions. Among the three metal centers, the two terminal Mg ions are five coordinate and have a square–pyramidal geometry, whereas the central Mg is four coordinate with a distorted tetrahedral geometry. The combination of ethyl and vinyl groups with sterically bulky aminoalkoxide ligands plays an important role in stabilizing the molecule. Abstract :